Weather information for smallholders - Yegbemey, Rosaine Nérice,Bensch, Gunther,Vance, Colin (RWI - Leibniz-Institut für Wirtschaftsforschung, 2021)
Weather conditions are an important determinant of agricultural factor input, particularly labor allocation. The availability of weather forecasts can therefore lead to efficiency gains in the form of cost decreases and productivity increases. We test the practical feasibility, the uptake, and the effect of providing basic weather forecasts in the rainy season on the labor productivity of smallholder farmers. For this purpose, we conducted a Randomized Controlled Trial as a pilot with monthly data collections involving 331 farmers across six villages in north Benin. We find that most farmers subscribe to the intervention and report satisfaction with the service. The impact estimates indicate positive and economically significant intention-to-treat and local average treatment effects on labor productivity for maize and cotton cultivation. These findings suggest that weather-related information and mobile phone outreach help smallholder farmers to better adapt to changing weather. Witterungsbedingungen beeinflussen wichtige Entscheidungen in der Landwirtschaft wie den Einsatz von Arbeitskräften. Die Verfügbarkeit von Wettervorhersagen kann daher zu Effizienzgewinnen in Form von Kostensenkungen und Produktivitätssteigerungen führen. In diesem Artikel testen wir die praktische Durchführbarkeit, die Akzeptanz und die Auswirkungen der Bereitstellung von Wettervorhersagen auf die Arbeitsproduktivität von Kleinbauern. Hierfür realisierten wir ein randomisiertes kontrolliertes Feldexperiment mit monatlichen Datenerhebungen in der Regenzeit unter 331 Bauern aus sechs Dörfern im Norden Benins. Im Rahmen dieser Pilotstudie stellten wir fest, dass die meisten Kleinbauern das Informationisangebot annehmen und mit der Dienstleistung zufrieden sind. Die ökonometrischen Schätzungen zeigen positive und wirtschaftlich signifikante Effekte auf die Arbeitsproduktivität im Mais- und Baumwollanbau. Diese Ergebnisse deuten darauf hin, dass wetterbezogene Informationen und der Einsatz von Mobiltelefonen den Kleinbauern dabei helfen können, sich besser an das sich ändernde Wetter anzupassen.
10.4419/9697308
Keywords: Graue Literatur; Pilot field experiment; climate and weather information; labor productivity; smallholder farming; information technology; impact evaluation